Nuclear localization and histone acetylation: a pathway for chromatin opening and transcriptional activation of the human β-globin locus - Schübeler, Dirk (Cold Spring Harbor Laboratory Press, 2000)
We have investigated the mechanism, structural correlates, and cis-acting elements involved in chromatin opening and gene activation, using the human β-globin locus as a model. Full transcriptional activity of the human β-globin locus requires the locus control region (LCR), composed of a series of nuclease hypersensitive sites located upstream of this globin gene cluster. Our previous analysis of naturally occurring and targeted LCR deletions revealed that chromatin opening and transcriptional activity in the endogenous β-globin locus are dissociable and dependent on distinct cis-acting elements. We now report that general histone H3/H4 acetylation and relocation of the locus away from centromeric heterochromatin in the interphase nucleus are correlated and do not require the LCR. In contrast, LCR-dependent promoter activation is associated with localized histone H3 hyperacetylation at the LCR and the transcribed β-globin-promoter and gene. On the basis of these results, we suggest a multistep model for gene activation; localization away from centromeric heterochromatin is required to achieve general hyperacetylation and an open chromatin structure of the locus, whereas a mechanism involving LCR/promoter histone H3 hyperacetylation is required for high-level transcription of the β-globin genes.